Impact of Opioid Restrictions During a Critical Drug Shortage Period: Interrupted Time Series for Institutional Opioid Utilization. Issue 1 (2nd September 2020) - Brokenshire, Samantha A; Lemon, Stephen J; Staley, Benjamin; Voils, Alissa; Hincapie-Castillo, Juan M
Abstract: Objectives: This study aimed to evaluate the impact of intravenous opioid product restrictions at an academic medical institution in an urban setting during the time of critical opioid shortages. We assessed the effect of ordering restrictions on inpatient opioid utilization measured by 1) changes in intermittent oral and injectable opioid product administration; 2) changes in total institutional opioid administration; and 3) changes in the utilization of individual restricted opioid agents. Methods: This study is a single-center retrospective analysis by interrupted time series of institutional opioid utilization from 07/2017 to 06/2018. Utilization was quantified using milligrams of intravenous morphine equivalent administered or dispensed per admitted patient. Restrictions were grouped into 10 distinct phases, which informed the interruptions in linear regression models. Results: Sequential restrictions during the study period led to shifts in use of individual agents but did not have a significant impact on overall total opioid utilization. "Soft" restrictions did not have a direct, statistically significant impact on medication use but did decrease utilization over time. In situations where a product was restricted with a "soft stop" followed by a "hard stop, " the "hard stop" directly reduced usage. Conclusions: Targeted ordering restrictions allowed the institution to redirect drug use according to clinical need without affecting the overall utilization. Clinical decision support led providers to choose therapeutically equivalent alternatives. The demonstrated effect of restrictions will guide institutions in the selection of "hard stop" or "soft stop" restrictions in response to future shortages.